ANALYSIS OF DISTRIBUTION SIMULATION OF SUSPENDED SLAB AND CYLINDER SUPERKONDUCTOR USING ELEMEN METHOD - Supardi Supardi (Jurnal Penelitian Saintek, 2006)
Investigation   of creation  of  ordered  parameter   distribution   on superconductor  material,  especially   cylinder form   has  been conducted. Distribution   of  ordered  parameter    inside  the  material   is  obtained  by applying  external  magnetic field  parallel  to the surface  of the material. When   the   external    magnetic   field    is   reduced    carefully,    ordered parameter  distribution  will create at a certain  value called He).The method  applied  to obtain the ordered parameter   distribution  isfinite element    method.    To  make   easy   in   computation    work,   be   applied FEMLAB    software.    The   software    works   under   MATLAB    running. Principles  of finite  element  method  have been covered  in FEMLABThe   result   of  the   numerical    simulation    show   in   line   between   the beginning   hypothesis   of researcher   and  computation   result.  Compared with previous  result, the result does not deviate significantly.